2019
DOI: 10.1111/jog.13991
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of Insulin‐like growth factor binding protein‐1, placental alpha‐microglobulin‐1, phenol and pH for the diagnosis of preterm premature rupture of membranes between 20 and 36 weeks

Abstract: Aim: Preterm premature rupture of membranes (PPROM) is responsible for approximately one-third of premature births worldwide, and although the diagnosis is often straightforward, this condition can still present difficulties. The purpose of this research was to compare the accuracy of several PPROM diagnostic tests. Methods: A total of 94 pregnant women with clinical suspicion of PPROM who were between 20 and 36 weeks of pregnancy were examined by vaginal speculum, and tests were performed for phenol, pH, insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
(29 reference statements)
0
1
0
1
Order By: Relevance
“…Moreover, mass spectrometry-based proteomic analysis of placental membranes collected after spontaneous labor (term or preterm) showed that ERP29 was detected only in term placentas 150 . The concentration of decidual IGFBP1 was shown to increase in vaginal secretions after fetal membrane rupture 151 , and an increased concentration of IGFBP1 in the cervicovaginal fluid has been proposed as a biomarker of PPROM [152][153][154] . These findings indicate that the amniotic fluid proteomic changes associated with term labor have biological plausibility and are translatable to the maternal circulation and across diverse cohorts of patients.…”
Section: Selective Expression Of Chemokine Receptors During T−cell Po...mentioning
confidence: 99%
“…Moreover, mass spectrometry-based proteomic analysis of placental membranes collected after spontaneous labor (term or preterm) showed that ERP29 was detected only in term placentas 150 . The concentration of decidual IGFBP1 was shown to increase in vaginal secretions after fetal membrane rupture 151 , and an increased concentration of IGFBP1 in the cervicovaginal fluid has been proposed as a biomarker of PPROM [152][153][154] . These findings indicate that the amniotic fluid proteomic changes associated with term labor have biological plausibility and are translatable to the maternal circulation and across diverse cohorts of patients.…”
Section: Selective Expression Of Chemokine Receptors During T−cell Po...mentioning
confidence: 99%
“…Порушення процесів інвазії, росту та розвитку трофобласта під час вагітності може бути основним фактором, що призводить до розладів гормонопродукувальної функції плаценти [9,10], а перепадам тиску у плацентарних судинах внаслідок ішемії-реперфузії належить центральна роль у патогенезі пускового механізму розвитку плацентарної дисфункції та передчасних пологів [11][12][13][14].…”
unclassified